End of project report: the screening for potential xylan, cellulose and lignin biodegradation activities from microbial communities in the South East Pahang peat swamp forest sediment and water (EDW B14-196-1081) - Mohd Omar, Suhaila (2016)
Previously, peat swamp forest was known as habitat that possesses low microbial activities due to extremely acidic, poor in nutrient, water-logged and anoxic environment. However, current research has proven that there is diversity of microbial communities in this harsh ecosystem. Therefore, in order to determine bacterial communities in this environment and their biotechnological potential, this study focuses on isolation of bacteria from Pekan peat swamp forest soil through cultivation and screening for lignocellulolytic activities on different agar-based medium. Selected isolates were also identified through 16S rRNA gene analysis. The incorporation of peat water in the cultivation medium has significantly increased the number of the isolates. Besides, the ability of the isolates to grow on all medium supplemented with various carbon sources including azure B, a synthetic model for lignin, indicates the presence of lignocellulase-producing bacteria. Forty-six different isolates have been screened and selected for 16S rRNA sequencing. Some of the identified bacteria are Burkholderia sp., Achromobacter sp., Streptomyces sp., Curtobacterium sp., Pantoea sp and Pandorea sp. The isolates that have shown promising lignocellulolytic activities will be subjected to agro waste biodegradation test in the future.